Tasikmalaya Batik - Aripin, Indri Yani; Nunuy Nurjanah; Ruswendi Permana (International Journal of Language and Culture, 2023)
The existence of batik production in the Tasikmalaya region, especially in Cigeureung, makes the cultural attraction of the Tasikmalaya area because of its production and distribution for so long. This paper is motivated by the lack of knowledge of the Tasikmalaya people themselves about the names of batik motifs, the philosophy of batik patterns, and the development of Tasikmalaya Batik from time to time to examine in detail and the background of Tasikmalaya Batik. Based on these problems, this paper aims to describe Tasikmalaya Batik. The method used in this paper is the descriptive method. The result of this paper is that the batik style in Tasikmalaya is influenced by the surrounding areas such as Garut, Cirebon, and others. However, separately it has its characteristics, namely the payung geulis and kelom geulis motifs.